How to teach safe landing after the jump? The use of biofeedback to minimize the shock forces generated in elements of modern dance - Gorwa, J.; Michnik, R.; Nowakowska-Lipiec, K. (Acta of Bioengineering and Biomechanics, 2021)
Purpose: The aim of the study was to assess the possible use of biofeedback (information on the course and values of ground reaction forces (GRF) during landing following the performance of a dance evolution) for training minimising impact loads after a jump in modern dance. Methods: The tests involved the analysis of a total of 60 expressive elements of modern dance performed by 5 soloists. The tests involved the recording of the vertical component of GRF (GRFz) vector using Kistler platform in the landing phase following the performance of modern dance jumps. The dancers performed the above-named jumps three times in successive tests: a reference test (without biofeedback) and the next two tests with biofeedback, after the obtainment of information about the vertical value of GRF. After each performance, the dancers watched a course of GRF and films showing the recorded landing phase. Results: Applying of a proposed didactic laboratory session led to: extension of contact time and of time preceding the obtainment of the maximum value of GRFz, reduction of the maximum values of the vertical components of the GRF, reduction of the loading rate of the ground reaction force, increase of an impulse of the vertical component of GRF in the entire stance phase and in the shock absorption phase. Conclusions: Proposed didactic laboratory session with biofeedback may result in the change of the post-jump shock absorption technique.